Biomechanics and energetics of running on uneven terrain - Voloshina, A. S.; Ferris, D. P. (The Journal of Experimental Biology, 2015)
In the natural world, legged animals regularly run across uneven terrain with remarkable ease. To gain understanding of how running on uneven terrain affects the biomechanics and energetics of locomotion, we studied human subjects (N=12) running at 2.3 m s-1 on an uneven terrain treadmill, with up to a 2.5 cm height variation. We hypothesized that running on uneven terrain would show increased energy expenditure, step parameter variability and leg stiffness compared with running on smooth terrain. Subject energy expenditure increased by 5% (0.68 W kg-1; P<0.05) when running on uneven terrain compared with smooth terrain. Step width and length variability also increased by 27% and 26%, respectively (P<0.05). Positive and negative ankle work decreased on uneven terrain by 22% (0.413 J kg-1) and 18% (0.147 J kg-1), respectively (P=0.0001 and P=0.0008). Mean muscle activity increased on uneven terrain for three muscles in the thigh (P<0.05). Leg stiffness also increased by 20% (P<0.05) during running on uneven terrain compared with smooth terrain. Calculations of gravitational potential energy fluctuations suggest that about half of the energetic increases can be explained by additional positive and negative mechanical work for up and down steps on the uneven surface. This is consistent between walking and running, as the absolute increases in energetic cost for walking and running on uneven terrain were similar: 0.68 and 0.48 W kg-1, respectively. These results provide insight into how surface smoothness can affect locomotion biomechanics and energetics in the real world.